IMPROVING THE METHODOLOGY OF TEACHING THE ENGLISH LANGUAGE THROUGH PROGRAMMED INSTRUCTIONAL TOOLS (International journal of artificial intelligence, 2026)
This article analyzes the issues of improving English language teaching methodology through programmed educational tools. The integration of modern information and communication technologies into the educational process creates new pedagogical opportunities for teaching English effectively. The article highlights the essence and advantages of programmed instruction as well as its role in developing students’ independent thinking, communicative competence, and language skills. Furthermore, the study examines ways of increasing educational effectiveness through the use of interactive platforms, multimedia resources, and digital technologies. The findings indicate that programmed educational tools enhance students’ motivation, provide individualized learning opportunities, and optimize the overall teaching and learning process in English language education.